Economic convergence and rent-seeking in Iran - Christian Dreger; Teymur Rahmani; Hans-Friedrich Eckey (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The neoclassical growth model predicts convergence of productivity or per capita output levels across regions. If participation in the labor force is constant, convergence of per capita income is implied. We investigate this hypothesis for the Iranian economy using data on demand deposits as a proxy for GDP. Furthermore, the analysis controls for the effects of rent seeking. Due to its impact on the allocation of resources, rent-seeking is likely an impediment to overall growth. The results support absolute ß-convergence across Iran's provinces and provide some evidence on the adverse effect of rent seeking on regional convergence.
Keywords: O43; O47; R11; 330; Regional convergence; rent-seeking; economic growth; Regionale Entwicklung; Entwicklungskonvergenz; Rent Seeking; Iran